GEEM - Grupo de Estudos do Ensino da Matemática e a Formação de Professores durante o Movimento da Matemática Moderna no Brasil - Lima, Flainer Rosa de (2006)
The objective of this research was to study all courses developed and realized by Grupo de Estudos do Ensino da Matemática GEEM for Mathematics Teachers from high school during Brazil Modern Mathematics Movement MMM that occurred along the 60 s and 70 s decades. This way we studied several thesis and dissertations about that matter and we analyzed a lot of documents from Personal Archive s Osvaldo Sangiorgi APOS, a teacher who was GEEM s president and a great MMM s promoter and implementer too. To complement all of these information we considerated some interviews realized with teachers that participated as formers and pupils from courses of this Group and all of those interviews was consummated on theoretic bases recommended by Bogdan & Biklen (1994) and Freitas (2002). The theoretic methodologies considerations was sustained on the next authors: Chartier (1991), that helped us on appropriation concept comprehension; Chervel (1990) and Julia (2001), whom we took as base their studying about scholar culture conceptions and the constitution of disciplines at schools; Le Goff (1992), who had helped us with monuments analyses and the transformation of its in documents; Nunes (2002/2003), that helped us with GEEM courses history analysis and with interviewed people reports; Vidal (2005 and 2005a), who supported us on analysis about practices of GEEM courses. We had considerated that teachers formations proposed by GEEM was based in a technique rationality perspective: all of courses was for training and its were supported on a apprenticement contents and with a kind of methodology that privileged the elaboration of a great quantity of exercises with reduced discussion about class practice, that the pedagogic component was not the great courses preoccupation